2012
DOI: 10.1039/c2sc21308g
|View full text |Cite
|
Sign up to set email alerts
|

Fusarisetin A: scalable total synthesis and related studies

Abstract: Fusarisetin A (1) is a recently isolated natural product that displays an unprecedented chemical motif and remarkable bioactivities as a potent cancer migration inhibitor. We describe here our studies leading to an efficient and scalable total synthesis of 1. Essential to the strategy was the development of a new route for the formation of a trans-decalin moiety of this compound and the application of an oxidative radical cyclization (ORC) reaction that produces fusarisetin A (1) from equisetin (2) via a bio-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 107 publications
0
47
0
3
Order By: Relevance
“…On the other hand, significant racemization at the C3 center was observed when a serine analog was cyclized under the same conditions en route to the synthesis of 1 . 15 This difference is attributed to the methyl hydroxy group of serine that inductively increases the acidity of the C3 proton. 21 Exposure to cerium ammonium nitrate (CAN) in acetic acid under oxygen atmosphere followed by reduction of the resulting endoperoxides, 22 produced fusarisetin analogs 8a–8d (18–25% overall yield).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, significant racemization at the C3 center was observed when a serine analog was cyclized under the same conditions en route to the synthesis of 1 . 15 This difference is attributed to the methyl hydroxy group of serine that inductively increases the acidity of the C3 proton. 21 Exposure to cerium ammonium nitrate (CAN) in acetic acid under oxygen atmosphere followed by reduction of the resulting endoperoxides, 22 produced fusarisetin analogs 8a–8d (18–25% overall yield).…”
mentioning
confidence: 99%
“…Initial cell-based evaluation of all fusarisetins (synthetic material, 15 1–100μM) was performed using a well-described scratch wound assay. 24 MDA-MB-231 cells were grown as a confluent monolayer, scratched and treated with analogs over a 24 hour period.…”
mentioning
confidence: 99%
“…12c, 16 Under these conditions, the IMDA reaction was slow (3 days for completion) and produced exclusively the endo -equatorial adduct 4 . 15 The results indicate that the catalysis was not effective in our substrate, presumably due to the presence of the C4 methyl group adjacent to the carbonyl group. This methyl group likely prevents the transiently formed iminium intermediate from assuming the geometry needed for the desired facial selectivity of IMDA, thus diminishing the ability of the catalyst to direct the stereochemical outcome of this reaction.…”
Section: Introductionmentioning
confidence: 84%
“…Previously, we demonstrated that triene 3 , synthetically available from (−)-citronellal ( 10 ) in 3 steps, undergoes an IMDA in the presence of Et 2 AlCl at −78 °C to produce the endo -equatorial product 4 . 15 We hypothesized that an organocatalytic process could overcome the inherent substrate selectivity of this system and favor construction of cycloadduct 5 , the one encountered in the structure of maklamicin. These studies are summarized in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation